2021
DOI: 10.1002/rrq.376
|View full text |Cite
|
Sign up to set email alerts
|

BIs forBunny”: Contested Sign‐Making and the Possibilities for Performing School Literacy Differently

Abstract: The tremendous interest in multimodality within the field of literacy education has challenged the verbocentric literacy landscape of schools. Research on multimodality in classroom spaces has suggested that combining and juxtaposing multiple sign systems is a generative act of transforming meanings. Yet, attention to entanglements of pedagogy and power has been rare in the research on students’ engagement with multimodality. In this article, we complicate the research on the generative potential of children’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Connecting with colleagues in education-adjacent fields such as special and gifted education or teaching English as an additional language may also advance our understanding of how multimodal composition might support the meaning-making work of all students. Theoretical frameworks or mash-ups (Kontovourki & Siegel, 2021) drawn from typically distinct areas of research may operationalize more completely the notion of multimodality as a democratic enterprise that seeks to honor the semiotic labor of all students—regardless of the modes, media, and materials they use (Cowan & Kress, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Connecting with colleagues in education-adjacent fields such as special and gifted education or teaching English as an additional language may also advance our understanding of how multimodal composition might support the meaning-making work of all students. Theoretical frameworks or mash-ups (Kontovourki & Siegel, 2021) drawn from typically distinct areas of research may operationalize more completely the notion of multimodality as a democratic enterprise that seeks to honor the semiotic labor of all students—regardless of the modes, media, and materials they use (Cowan & Kress, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite examining the ways in which children's literate bodies are regulated, researchers have nevertheless suggested that looking closely at children's performances in everyday classroom encounters enables seeing these as fragmented, manifold, and thus possible to redefine literacy and literacy learning (e.g. Dyson, 2003, 2008; Henning, 2019; Kontovourki & Siegel, 2022). Focusing particularly on children's talk and noise in an early primary classroom, Dernikos (2020) suggested that the regulation of sounds cites hegemonic, raced and classed discourses but is never fixed.…”
Section: Talk Discourse and Noise In Schooled Bodiesmentioning
confidence: 99%
“…Accordingly, one can identify a skills‐based, sequential notion of comprehension; the evaluative workings of literacy teaching; particular definitions of dialogic engagement in learning; the prioritisation of eloquence (regardless of context); and the hierarchisation of mainstream and non‐mainstream varieties. All these work together and onto human and nonhuman bodies to foreground language (oral, written and performed) as the primary object of school literacy and pedagogy, regardless of teachers' attempts to integrate in the assemblage digital tools and media; hence indexing monolingual, monomodal, monocultural notions of literacy that are repeatedly reinforced through official policies and curricula (see Kontovourki & Siegel, 2022 and Mills & Stornaiuolo, 2018 for critiques). As discourses that permeate schooling and literacy in school, these become immaterial forces that regulate and confine being school‐literate.…”
Section: Talking School Discourse: a Reading In Three Movesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1994, Rowe leveraged semiotics to position preschoolers’ scribblings as meaning-filled written expressions thus laying the groundwork for literacy scholars to embrace multimodal texts (see also Clark, 1990; Leland & Harste, 1994; Short & Kauffman, 2000). In the ensuing years, literacy scholars similarly drew on semiotics to consider the reading and writing that occur when users encounter multimodal digital texts (see Baker, 2000; Gillen, 2014; Kontovourki & Siegel, 2021; Kress, 2010; Serafini, 2014; Siefkes, 2015). In 1995, I observed Sally as she researched Alaska.[To learn about Alaska,] Sally…read her social studies textbook…which incorporated alphabetic text, illustrations, and photographs.…”
Section: Threads Through Timementioning
confidence: 99%